2014
DOI: 10.15406/jpcpy.2014.01.00040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Khat Chewing Among Atse Fasil Campus Students, University of Gondar, North West Ethiopia June 2013

Abstract: Introduction: Khat is a shrub or tree its leaves have been chewed for centuries in the Eastern part of Africa and the Arabian Peninsula. Globally, Khat chewing habit is being a hot issue of discussion and spreading at an alarming rate in young generation, especially in higher institutions; where there are intensive academic activities are more intended. Similarly in Ethiopia it is consumed by some population groups commonly youths. It has a reported negative economic and health impact on the individuals engagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This finding shows that poly-substance use behavior can be found among students with a khat chewing habit [15]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding shows that poly-substance use behavior can be found among students with a khat chewing habit [15]. …”
Section: Discussionmentioning
confidence: 95%
“…dizziness, impaired cognitive functioning, fine tremor, insomnia, and headaches. Khat chewers have a significantly higher mortality rate due to chronic illnesses such as heart disease and stroke than non-khat chewers, and khat chewing among youths can increase the risk of contracting human immunodeficiency virus (HIV) and other sexually transmitted diseases [1522]. …”
Section: Introductionmentioning
confidence: 99%
“…This feeling of well being may affect their health seeking behavior and to come late for diagnosis. Moreover, Khat chewers believe that Khat use for relieving stress and pain [ 24 ]. A study by Glenice and Ramps showed that khat chewers in Yemen believed Khat was beneficial for mild ailments like headache, fevers and depression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the general formula for comparison of two means i.e. n = (S 1 2 +S 2 2 ) (Z α/2 + Z β ) 2 /d 2 where, n: sample size, Z α/2 : Z-value corresponding to 95% confidence interval, Z β : Z-value corresponding to one-sided power of 95%, S 1 : standard deviation among chewers, S 2 : standard deviation among non-chewers and d: minimum detectable difference 22. The sample size was estimated by considering the mean (standard deviation) of diastolic blood pressure as 75.0 (11.6) mmHg among Khat chewers and 72.9 (11.7) mmHg among non-chewers reported in a previous study,8 95% confidence interval (CI), 95% power, minimum detectable difference of 2.1 mmHg and design effect of 1.5.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted in Butajira town, Ethiopia, 50% of adults aged 15 years or older were found to be regular Khat chewers 21. Despite its adverse health impact, the prevalence of Khat chewing seems to be increasing 22…”
Section: Introductionmentioning
confidence: 99%